ASSESSMENT OF ENVIRONMENTAL OF LANDSCAPES «GREAT HODOSIVSKYI MOUND» IN KYIV REGION (paleopedological aspect) - ПАРХОМЕНКО, О. Г. (Man and Environment. Issues of Neoecology, 1970)
There has been investigated the soils buried under the body of the shaft of the early iron age and modern (background).There has also been carried out comparing them to assess the environmental condition of the landscape with in which the profiles of soil are situated. It has been defined that soil formation processes that underpinned the modern profiles and buried (ancient) soil, are characterized by a combination of processes of capable of the accumulation of substances, radionuclides and heavy metals. It has been determined that the amount of heavy metals lies within background values. The obtained data testify the fact that in the modern (background) soil the heavy metals are being accumulated in arable horizon. It has been fixed that in the modern soil the concentration of heavy metals in profile is a higher than in buried one. This shows the change of conditions and factors that affect geochemistry of the landscape for a long time of their formation